The influence of organizational climate, workload and role conflict on emotional exhaustion of teachers and employees of elementary schools in the village of Tanjung Paling Serumpun, Sungai Penuh City - Helia, Suhelmi; Khamri, Alis (Institute of Computer Science (IOCS), 2024)
This study aims to see the effect of organizational climate on emotional exhaustion, workload on emotional exhaustion, (3) role conflict on emotional exhaustion and organizational climate, workload and role conflict jointly affect the emotional exhaustion of teachers and elementary school employees in Tanjung Paling Serumpun Village, Sungai Penuh City. The sample used in this study amounted to 39 people with the sampling technique, namely total sampling. Data analysis techniques used multiple linear regression. The results of this study indicate that organizational climate has a positive and significant effect on emotional exhaustion, workload has a positive and significant effect on emotional exhaustion, role conflict has a positive and significant effect on emotional exhaustion of teachers and elementary school employees in Tanjung Paling Serumpun Village, Sungai Penuh City and organizational climate, workload and role conflict together have a positive effect on emotional exhaustion of teachers and elementary school employees in Tanjung Paling Serumpun Village, Sungai Penuh City.